Professional Ethics of Notaries in Promotion on Social Media the Impact and Implications of Fake Testimonials - St Syarifah; Pujiyono Pujiyono (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
The professional ethics of notaries serve as a moral and legal foundation to maintain public trust in the notarial profession. In the digital era, social media is frequently used for promotion, but this practice often conflicts with ethical codes, particularly regarding the use of fake testimonials. Such promotions can harm public trust and the reputation of the notarial profession. This study employs a qualitative approach with a descriptive-analytical method to examine the impact of fake testimonials in notary promotions on social media. The analysis reveals that fake testimonials potentially violate ethics and laws, leading to administrative sanctions or license revocation. To safeguard professional integrity, strict supervision by the Notary Honorary Council (MKN) and a comprehensive understanding of ethical promotion boundaries are required.